CMM industries - Grimshaw, Damian (SAGE knowledge. Cases., 2016)
CMM Industries is a US-manufacturing engineering company with major operations in Europe. In this context, it is used as an example of challenging international human resources (HR) management. More specifically, we observe the various countries' opinions on the creation of a union, after the HR's shift towards centrally driven policies in the areas of industrial relations and the management of pay and performance.